FVC, FEV1, FEV1/FVC % and their Relationship with EF% in Patients with Chronic Heart Failure - Mollika, Rono; Begum, Shelina; Hoque, Md Harisul; Afreen, Khandaker Nadia; Sharmin, Elora; Ahmed, Sheikh Foyez (University Heart Journal, 2020)
Background: Chronic heart failure (CHF) causes multiple lung complications and lung functions are reduced in CHF patients. Objective: To observe FVC, FEV1, FEV1/FVC% and their relationship with EF% in patients with chronic heart failure. Methods: This cross sectional study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, during 2016. For this, 60 diagnosed stable male, aged 35-65 years CHF patients were randomly selected from the Cardiology Department of BSMMU, Dhaka. On the basis of staging of the disease (Stage C) and New York Heart Association (NYHA) functional classification, the study subjects were divided into two groups, 30 patients of NYHA Class- I and 30 patients of NYHA class –II. Thirty (30) apparently healthy Age, Sex and BMI matched subjects were taken as control. To assess the ventilatory function, Forced vital capacity (FVC), Forced expiratory volume in 1st second (FEV1), Forced expiratory ratio (FEV1/FVC%) of all subjects were measured by a portable Digital Spirometer. Again, Ejection fraction (EF%) ranged (≥35% to ≤50%) were measured by Echocardiogram to observe left ventricular function of the heart. For statistical analysis, Independent sample‘t’ test and Pearson’s correlation co-efficient test was performed by using SPSS for windows version-16 & p≤0.05 was accepted as level of significance. Results: The mean percentage of predicted values of FVC and FEV1 were significantly lower but FEV1/FVC% was significantly higher in CHF patients comparison to the healthy control. All the study variables were significantly lower in patients of NYHA class–II as compared to patients of NYHA class–I. 73.33% CHF patients had restrictive, 10.00% small airway obstruction and 16.67% combined restrictive and small airway obstruction feature. In addition, FVC and FEV1 (p<0.05) was positively and FEV1/FVC% (p<0.05) negatively correlated with EF% in chronic heart failure patients. Conclusion: Left ventricular dysfunction may be silently associated with decrease ventilatory function mainly restrictive type of pulmonary disorder. University Heart Journal Vol. 16, No. 2, Jul 2020; 59-64